CORP: Ultrasound assessment of vascular function with the passive leg movement technique - Gifford, Jayson R.; Richardson, Russell S. (Journal of applied physiology (1985), 2017)
As dysfunction of the vascular system is an early, modifiable step in the progression of many cardiovascular diseases, there is demand for methods to monitor the health of the vascular system noninvasively in clinical and research settings. Validated by very good agreement with more technical assessments of vascular function, like intra-arterial drug infusions and flow-mediated dilation, the passive leg movement (PLM) technique has emerged as a powerful, yet relatively simple, test of peripheral vascular function. In the PLM technique, the change in leg blood flow elicited by the passive movement of the leg through a 90° range of motion is quantified with Doppler ultrasound. This relatively easy-to-learn test has proven to be ≤80% dependent on nitric oxide bioavailability and is especially adept at determining peripheral vascular function across the spectrum of cardiovascular health. Indeed, multiple reports have documented that individuals with decreased cardiovascular health such as the elderly and those with heart failure tend to exhibit a substantially blunted PLM-induced hyperemic response (~50 and ~85% reduction, respectively) compared with populations with good cardiovascular health such as young individuals. As specific guidelines have not yet been put forth, the purpose of this Cores of Reproducibility in Physiology (CORP) article is to provide a comprehensive reference for the assessment and interpretation of vascular function with PLM with the aim to increase reproducibility and consistency among studies and facilitate the use of PLM as a research tool with clinical relevance.